1996
DOI: 10.1042/bj3200571
|View full text |Cite
|
Sign up to set email alerts
|

F1F0-ATPase, early target of the radical initiator 2,2′-azobis-(2-amidinopropane) dihydrochloride in rat liver mitochondria in vitro

Abstract: This study was designed to determine which enzyme activities were first impaired in mitochondria exposed to 2,2'-azobis-(2-amidinopropane) dihydrochloride (AAPH), a known radical initiator. EPR spin-trapping revealed generation of reactive oxygen species although malondialdehyde formation remained very low. With increasing AAPH concentrations, State-3 respiration was progressively depressed with unaltered ADP/O ratios. A top-down approach demonstrated that alterations were located at the phosphorylation level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, previous studies have shown that ADP/ATP translocase and F 1 F 0 ATPase are highly sensitive to ROS [4,10,21,35,39]. A reduced V max of these processes would explain the accentuated effect of ROS at higher flux.…”
Section: Discussionmentioning
confidence: 95%
“…However, previous studies have shown that ADP/ATP translocase and F 1 F 0 ATPase are highly sensitive to ROS [4,10,21,35,39]. A reduced V max of these processes would explain the accentuated effect of ROS at higher flux.…”
Section: Discussionmentioning
confidence: 95%
“…Another study (33) showed that the antioxidant activity of different commercial wines against LDL oxidation is not a property of a single phenol compound but that the activity is widely distributed among phytochemical substances, including resveratrol. The low activity of resveratrol as an antioxidant was also shown by the fact that it completely failed to prevent the decrease in rat liver state-3 mitochondrial respiration caused by the radical initiator 2,2-azobis-(2-amidinopropane) dihydrochloride (34). It was shown recently that red wine consumption in volunteers did not affect oxidizability of LDL (35), thereby suggesting that the activity of wine in reducing coronary artery disease may not be related to the antioxidant activity of wine compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation and use of permeabilized yeast spheroplasts was made according to Averet et al (14). Measurement of respiration (in the presence of 6 mM NADH) was made with an oxygen electrode; measurement of mitochondrial membrane potential was determined with a tetraphenylphosphonium (TPP ϩ ) electrode as described elsewhere (15) under conditions where the ⌬pH component was low and did not vary. To compare different spheroplast preparation, the experiments were performed using the same amount of respiratory chains as determined by the maximal respiratory rate in presence of 1 M FCCP uncoupler.…”
Section: Methodsmentioning
confidence: 99%